L'utilisation des enquetes integrees pour le recensement des ressources et le suivi de l'evolution des systemes pastoraux en Afrique au sud du Sahara - Leeuw, P.N. de; Milligan, K. (1984)
Reviews various approaches and techniques used in a number of sub-Saharan African countries to collect and analyze data on large-scale ecological changes with particular reference to remote sensing and monitoring techniques in resource inventory; suggests ways to build more effective data bases.